Leadership plain and simple - Redcliffe, steve (Financial Times Prentice Hall, 2012)
Leadership isn't complicated - keep it simple and make it count. This new edition of Steve Radcliffe's uniquely powerful, successful and practical framework will show you how to develop faster as a more confident and capable leader. This compact, instantly-applicable guide to developing leadership skills contains practical insights, straightforward actions and plain guidelines to accelerate your growth as a leader.